2018
DOI: 10.1021/acs.est.8b01393
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and Speciation Analysis of Silver Nanoparticles of Dietary Supplement in Simulated Human Gastrointestinal Tract

Abstract: Knowledge of the physicochemical properties of ingestible silver nanoparticles (AgNPs) in the human gastrointestinal tract (GIT) is essential for assessing their bioavailability, bioactivity, and potential health risks. The gastrointestinal fate of AgNPs and silver ions from a commercial dietary supplement was therefore investigated using a simulated human GIT. In the mouth, no dissolution or aggregation of AgNPs occurred, which was attributed to the neutral pH and the formation of biomolecular corona, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 42 publications
5
47
0
Order By: Relevance
“…The authors observed no aggregation of the Ag NPs or dissolution in the simulated saliva containing mucin and α‐amylase, and attributed this stabilization to the biomolecular corona formation on the NP surface. [ 101 ] In good agreement, minimal aggregation and dissolution of Ag NPs was reported in authentic saliva, a phenomenon the authors of the study attributed to macromolecular corona formation on the Ag NPs surface. [ 102 ] In the gastric phase, extensive oxidative dissolution of Ag NPs (≈72 wt% of total Ag NPs) was observed due to the high acidity and Cl − concentration, which was noted to be slowed down in the presence of mucin.…”
Section: The Transformation Of Food Relevant Enms Across Their Life Csupporting
confidence: 63%
See 4 more Smart Citations
“…The authors observed no aggregation of the Ag NPs or dissolution in the simulated saliva containing mucin and α‐amylase, and attributed this stabilization to the biomolecular corona formation on the NP surface. [ 101 ] In good agreement, minimal aggregation and dissolution of Ag NPs was reported in authentic saliva, a phenomenon the authors of the study attributed to macromolecular corona formation on the Ag NPs surface. [ 102 ] In the gastric phase, extensive oxidative dissolution of Ag NPs (≈72 wt% of total Ag NPs) was observed due to the high acidity and Cl − concentration, which was noted to be slowed down in the presence of mucin.…”
Section: The Transformation Of Food Relevant Enms Across Their Life Csupporting
confidence: 63%
“…The structural and physicochemical properties of commercial Ag ENMs, specifically their interfacial properties, could be expected to differ from those of laboratory‐synthesized AgNPs, and might contribute to contrasting transformation outcomes. In a recent study, Wu et al [ 101 ] subjected a realistic concentration of commercial Ag NPs based dietary supplement to a sequential cascade of salivary, gastric, and intestinal fluid treatment, to understand their transformation in GIT. The authors observed no aggregation of the Ag NPs or dissolution in the simulated saliva containing mucin and α‐amylase, and attributed this stabilization to the biomolecular corona formation on the NP surface.…”
Section: The Transformation Of Food Relevant Enms Across Their Life Cmentioning
confidence: 99%
See 3 more Smart Citations